2016
DOI: 10.1098/rsob.160197
|View full text |Cite
|
Sign up to set email alerts
|

SBE6: a novel long-range enhancer involved in driving sonic hedgehog expression in neural progenitor cells

Abstract: The expression of genes with key roles in development is under very tight spatial and temporal control, mediated by enhancers. A classic example of this is the sonic hedgehog gene (Shh), which plays a pivotal role in the proliferation, differentiation and survival of neural progenitor cells both in vivo and in vitro. Shh expression in the brain is tightly controlled by several known enhancers that have been identified through genetic, genomic and functional assays. Using chromatin profiling during the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
(72 reference statements)
1
29
0
1
Order By: Relevance
“…We have shown previously that SBE6 is involved in the proper induction of Shh expression during NPC differentiation, and that there is a prominent gain of H3K4me1 and H3K27ac at this regulatory element during differentiation to Sox1+ve NPCs (Benabdallah et al, 2016). FISH showed that the increased Shh-SBE6 inter-probe distances are abolished in NPCs derived from SBE6 -/-ESCs ( Figure 2A).…”
Section: Shh-sbe6 Chromosome Unfolding Requires Sbe6 and Occurs In Vivomentioning
confidence: 67%
See 4 more Smart Citations
“…We have shown previously that SBE6 is involved in the proper induction of Shh expression during NPC differentiation, and that there is a prominent gain of H3K4me1 and H3K27ac at this regulatory element during differentiation to Sox1+ve NPCs (Benabdallah et al, 2016). FISH showed that the increased Shh-SBE6 inter-probe distances are abolished in NPCs derived from SBE6 -/-ESCs ( Figure 2A).…”
Section: Shh-sbe6 Chromosome Unfolding Requires Sbe6 and Occurs In Vivomentioning
confidence: 67%
“…This suggests that a large-scale chromatin unfolding occurs upon Shh neural induction and that this is limited to the region 300kb 5' of the Shh TSS. It is noteworthy that, within this 300kb region, the most prominent peaks of H3K3me1 and H3K27ac gained during this NPC differentiation programme occur at SBE6, and that SBE6 is required for full induction of Shh during this differentiation programme (Benabdallah et al, 2016). The increased separation between Shh and SBE6/SBE4 upon Shh induction does not seem compatible with the formation of a chromatin loop between Shh and these two neural enhancers.…”
Section: Increased Nuclear Separation Of Shh and Shh-brain-enhancersmentioning
confidence: 90%
See 3 more Smart Citations